Tennis Serve Speed in Relation to Isokinetic Shoulder Strength, Height, and Segmental Body Mass in Junior Players - Vacek, Jan; Vagner, Michal; Malecek, Jan; Stastny, Petr (Journal of functional morphology and kinesiology, 2025)
Objectives: The relationship between the isokinetic maximal strength of internal or external shoulder rotation and serve speed in tennis is well established, yet the influence of segmental mass, height, and high-speed shoulder rotation strength on serve performance in junior players remains unclear. This study aimed to investigate the relationship between concentric or eccentric isokinetic shoulder strength, segmental mass, height, and first-serve speed aimed at the T-target zone. Methods: Fifteen male junior competitive tennis players (mean ± SD: age 15.9 ± 0.9 years; height: 180.1 ± 7.2 cm; body mass: 66.1 ± 5.7 kg) were assessed for maximal isokinetic strength during concentric and eccentric internal and external shoulder rotations. Segmental mass (arm, leg, and trunk) was measured using dual-energy X-ray absorptiometry, and serve speed was recorded using a radar gun. Results: Concentric shoulder rotations at 210°/s demonstrated significant positive correlations with serve speed for both external (ρ = 0.71, p ≤ 0.01) and internal rotation (ρ = 0.61, p ≤ 0.05). Although lean arm mass partially mediated the relationship between shoulder strength and serve speed (indirect effect = 0.502, 95% CI: -0.156 to 1.145), this mediation effect was not statistically significant. Height was moderately correlated with serve speed (ρ = 0.68, p ≤ 0.01) but did not moderate the relationship between shoulder strength and serve speed. Conclusions: Concentric shoulder strength at higher angular velocities and segmental mass contribute to serve speed in junior tennis players. While height provides structural advantages, strength and lean mass play important roles, emphasizing the need for targeted training programs.